“QuanTour” illuminates Europe with single photons: celebrating the International Year of Quantum Science and Technology 2025 - Fei Ding (Light: Science & Applications, 2025)
Abstract Witness the journey of a solid-state quantum light source travelling across Europe and beyond—like an Olympic torch relay in the quantum realm.